2018
DOI: 10.1016/j.nicl.2018.06.017
|View full text |Cite
|
Sign up to set email alerts
|

Predicting seizure outcome of vagus nerve stimulation using MEG-based network topology

Abstract: Vagus nerve stimulation (VNS) is a low-risk surgical option for patients with drug resistant epilepsy, although it is impossible to predict which patients may respond to VNS treatment. Resting-state magnetoencephalography (rs-MEG) connectivity analysis has been increasingly utilized to investigate the impact of epilepsy on brain networks and identify alteration of these networks after different treatments; however, there is no study to date utilizing this modality to predict the efficacy of VNS treatment. We i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
38
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(52 citation statements)
references
References 49 publications
(75 reference statements)
5
38
0
1
Order By: Relevance
“…Interestingly, one commonality in reported biomarkers of VNS response was that more normative neurophysiological states are more likely to result in good response to VNS. In EEG studies, decreased segregation of frequency bands was reported in VNS nonresponders, whereas responders more closely resembled healthy controls, suggesting a decrease in the robustness and specialization of global brain networks in nonresponders 20 . Similarly, DTI microstructure more closely resembling normal controls was associated with greater responsiveness in a pediatric cohort undergoing VNS 9 .…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations
“…Interestingly, one commonality in reported biomarkers of VNS response was that more normative neurophysiological states are more likely to result in good response to VNS. In EEG studies, decreased segregation of frequency bands was reported in VNS nonresponders, whereas responders more closely resembled healthy controls, suggesting a decrease in the robustness and specialization of global brain networks in nonresponders 20 . Similarly, DTI microstructure more closely resembling normal controls was associated with greater responsiveness in a pediatric cohort undergoing VNS 9 .…”
Section: Discussionmentioning
confidence: 93%
“…In EEG studies, decreased segregation of frequency bands was reported in VNS nonresponders, whereas responders more closely resembled healthy controls, suggesting a decrease in the robustness and specialization of global brain networks in nonresponders. 20 Similarly, DTI microstructure more closely resembling normal controls was associated with greater responsiveness in a pediatric cohort undergoing VNS. 9 These findings are consistent with previous work showing that greater deviations from normative brain network structure portends worse outcomes.…”
Section: Biomarkers Demonstrate That Normative States Are Associatementioning
confidence: 89%
See 2 more Smart Citations
“…The antiepileptic effect of VNS could be related to a diffuse cortical modulation of synchronization, as suggested in previous studies with animal models (Chase et al, 1967;Magnes et al, 1961;Zanchetti et al, 1952), electroencephalography (EEG) (Bodin et al, 2015), stereoelectroencephalography (SEEG) (Bartolomei et al, 2016), magnetoencephalography (MEG) (Babajani-Feremi et al, 2018;Mithani et al, 2019), or imaging evaluations in humans (Ibrahim et al, 2017;Mithani et al, 2019). Combining diffusion tensor imaging and resting-state MEG recordings in responder (R) and nonresponder (NR) patients, a multimodal connectomic prediction algorithm for VNS has been proposed (Mithani et al, 2019).…”
mentioning
confidence: 80%